Synthesis of isophoric concentric ring arrays with multiple constraints. Issue 19 (26th July 2019) - Dai, Dingcheng; Yao, Minli; Jin, Wei; Zhang, Fenggan
Abstract : Sparse method provides an efficient way for antenna systems to achieve low cost, weight, and complexity. However, the synthesis of sparse arrays always limited to multiple constraints, which include aperture, number of elements, and minimum elements spacing. The characteristic that element number in each ring of concentric ring array (CRA) is related to its ring radius, which is different from square or rectangle planar arrays, leads to a complex constrained optimisation problem for the synthesis. Here, a novel vector mapping method for e‐design of sparse CRA is proposed. According to the mapping functions established here, the ring radius and element number can be mapped by two variable vectors with only upper and lower boundaries. Thus, the strong constrained optimisation problem can be transformed to the unconstrained. Numerical examples show the effectiveness of the proposed method, which provides layouts of elements able to produce lower sidelobe level that satisfy multiple requirements.